Peran Budaya Literasi dalam Meningkatkan Minat Baca Siswa Di Sekolah Dasar - Riska Riska; Muhammad Syukur (Lembaga Pengembangan Kinerja Dosen, 2023)
Literacy is the capacity to comprehend, gain access to, and effectively utilise information through speaking, writing, and reading activities. It is indisputable that there are encouraging and discouraging aspects throughout the implementation of the School Literacy Movement in order to improve kids' interest in reading, particularly in elementary schools. This study aimed to investigate the role of literacy activities, educational hurdles, and initiatives to boost reading motivation in elementary school students. This study is qualitative in nature. Principals of schools, as well as pupils and instructors at Inpresi Kadundungan Elementary School, participated in the study. ways for gathering data through observation, writing, and interviewing. Based on the study's findings, it can be concluded that literacy-related activities help kids become more interested in reading and help teachers and administrators work to remove obstacles to literacy-related activities.